Visitor experience in digital museums: dimensions, scale development, and validation - Zhu, Lanxin; De Costa, Feroz; Yasin, Megat Al-Imran (Redfame Publishing Inc., 2024)
Purpose – Providing visitors with excellent experience is a key challenge faced by digital museum development. However, the dimensionality of visitor experience in digital museums is under-explored, and there is a scarcity of survey scales for measuring multiple dimensions of visitor experience in digital museums. This study aimed to explore the dimensionality of visitor experience in digital museums and develop a survey scale for measuring multiple dimensions of visitor experience in digital museums. Design/methodology/approach – This study adopted a mixed method by interviewing 12 digital museum visitors and implemented a questionnaire survey with 982 visitors. The qualitative data was analysed using a thematic analysis technique while the quantitative data was analysed based on exploratory factor (EFA) analysis and confirmatory factor analysis (CFA). Findings – Based on qualitative results, this study developed a new dimension model for visitor experience in digital museums based on interview research that consists of five experience dimensions: technological, social, emotional, cognitive, and behavioral experience. Accordingly, this study also designed a specialized survey scale to measure these five dimensions. The scale’s validity and reliability were verified and purified. This new scale can be used by future survey research on digital museums from a visitor perspective. Originality/value – This is the first study that empirically explored the dimensionality of visitor experience in digital museums. The study also developed a first survey scale specifically for measuring multiple dimensions of visitor experience in digital museums.